The contribution of the region of Kharrata and its environs to the military activity of the revolution through testimonies (1954-1962) - merah, Hadi (The Algerian Historical Journal, 2026)
The region of Kharrata and its surroundings were among the ones that contributed to the military fighting of the Great liberation Revolution, as the region of Kharrata and its surroundings are considered a link between the third and second historical districts. This region gave the most wonderful models in confronting French colonialism, through political and military action, and this has appeared through the emergence of many revolutionary elements, whether as fighters or assailants, they had an active role in the revolution of the region. The region also witnessed torture centers, detention centers, and camps. The region also witnessed the most important battles and clashes with the French enemy. The research aimed to shed light on the history of the Algerian revolution in the region, the strong desire to revive the memory of the ancestors of the region and highlight their sacrifices.